The process of facilities management in public school at Perak Tengah District / Khairul Azman Ali and Md Yusof Hamid - Ali, Khairul Azman; Hamid, Md Yusof (2019)
The public school is a place where students going to get all the knowledge. The school management and District Educational Office are the first parties who responsible for managing the facilities at public school. There are several processes that must be undertaken by certain parties to ensure that school facilities are in good condition and maintained. The problem that found in this research is efficiency of facilities management process, budget for facilities management and understanding facilities management process. The aim of this research is to study the existing facilities management process in Public School at Perak Tengah District. The method that is used for this research is primary data such as interview and questionnaire, for the secondary data such as books, journals, newspaper. The result revealed that the long process of determining and providing budget has caused maintenance work delayed on public school. The result on both quantitative and qualitative concluded that performance within process school facility management needs to be improved.